2023
DOI: 10.1080/21645515.2023.2291243
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of community pharmacists on vaccination, barriers and willingness to implement community pharmacy-based vaccination services in Ethiopia

Solome Tadele,
Bezawit Negash Demissie,
Melaku Tileku Tamiru
et al.

Abstract: This study aimed to evaluate the knowledge and attitudes of community pharmacists (CPs) on vaccination and assess the barriers and willingness to implement community pharmacy-based vaccination services (CPBVS) in Ethiopia. An online cross-sectional study was conducted on 423 CPs in Ethiopia, and questionnaires were distributed to CPs through the Ethiopian Pharmaceutical Association telegram group and e-mail invitations. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 27. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The 34 studies selected for this review were conducted in 19 countries across 5 WHO regions ( Table 2 ). The selected literature included eight studies from the United States [ 3 , 27 , 28 , 30 , 34 , 40 , 51 , 52 ]; five from Canada [ 29 , 35 , 36 , 37 , 53 ]; three from Jordan [ 41 , 54 , 55 ]; three from Nigeria [ 56 , 57 , 58 ]; two each from Lebanon [ 38 , 59 ], Malaysia [ 60 , 61 ] and Indonesia [ 62 , 63 ]; and one each from Estonia [ 64 ], France [ 65 ], Italy [ 66 ], Austria [ 33 ], Serbia [ 31 ], Bulgaria [ 31 ], Albania [ 31 ], Saudi Arabia [ 32 ], Romania [ 31 ], Poland [ 39 ], Ethiopia [ 67 ] and Thailand [ 68 ]. The study by Turcu-Stiolica et al reported research conducted in four countries: Romania, Serbia, Albania and Bulgaria [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 34 studies selected for this review were conducted in 19 countries across 5 WHO regions ( Table 2 ). The selected literature included eight studies from the United States [ 3 , 27 , 28 , 30 , 34 , 40 , 51 , 52 ]; five from Canada [ 29 , 35 , 36 , 37 , 53 ]; three from Jordan [ 41 , 54 , 55 ]; three from Nigeria [ 56 , 57 , 58 ]; two each from Lebanon [ 38 , 59 ], Malaysia [ 60 , 61 ] and Indonesia [ 62 , 63 ]; and one each from Estonia [ 64 ], France [ 65 ], Italy [ 66 ], Austria [ 33 ], Serbia [ 31 ], Bulgaria [ 31 ], Albania [ 31 ], Saudi Arabia [ 32 ], Romania [ 31 ], Poland [ 39 ], Ethiopia [ 67 ] and Thailand [ 68 ]. The study by Turcu-Stiolica et al reported research conducted in four countries: Romania, Serbia, Albania and Bulgaria [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment conducted across nine domains showed most (n = 21, 61.8%) of the included studies with an overall low risk of bias (quality score = 7–8) [ 3 , 27 , 28 , 32 , 33 , 35 , 36 , 37 , 38 , 40 , 52 , 53 , 54 , 55 , 56 , 59 , 60 , 61 , 66 , 67 , 68 ]. About a third (n = 13, 38.2%) of the studies had a moderate risk of bias (quality score = 6) [ 29 , 30 , 31 , 34 , 39 , 41 , 51 , 57 , 58 , 62 , 63 , 64 , 65 ], while none showed a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a concerning finding as other studies have reported varied levels of knowledge in their sample. Studies from Lebanon and Ethiopia reported contrasting results wherein more than 90% of the pharmacists in their sample had good knowledge of vaccines [ 16 , 27 ]. Another study from Malaysia reported moderate knowledge level among half of the participating pharmacists [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, many other have reported legal liability as the most critical barrier in provision of immunization service at community pharmacies [ 20 , 32 34 ]. However, other studies from Ethiopia and Jordan have reported lack of authorization as the most common barrier for providing vaccination service at community pharmacies [ 27 , 35 ]. Therefore, it important to review and update the regulations in Saudi Arabia in regard to authorizing pharmacists to administer vaccines.…”
Section: Discussionmentioning
confidence: 99%